Bimbingan Bahasa Arab Tingkat Dasar Pada Anak Asuh Panti Asuhan Yatim dan Miskim Muhammadiyah Kedungwuni Kabupaten Pekalongan - Rosanti, Cholisa; Fuad, Asfal; Setianto, Gigih; Sulaiman, Muh Andi (Yayasan Daarul Huda Kruengmane, 2024)
Basic Arabic language guidance for foster children of the Muhammadiyah Kedungwuni Orphanage, Pekalongan Regency is an educational program that aims to provide basic understanding of Arabic to foster children living in the orphanage. This program is implemented with the aim of providing knowledge of Arabic to foster children so that they can understand and master the language effectively as a support for Arabic language subjects in schools. In its implementation, this basic Arabic language guidance is carried out systematically and structured, by paying attention to the level of understanding and ability of Arabic of each foster child. The teaching methods used in this program include active, interactive, and experience-based learning through the presentation of materials with guidance on interpreting, translating vocabulary and sentences, as well as providing guidance on understanding Arabic language rules, so that foster children can learn Arabic more easily and enjoyably. The evaluation results of the implementation of the basic Arabic language guidance program for foster children of the Muhammadiyah Kedungwuni Orphanage, Pekalongan Regency showed a significant increase in the understanding and mastery of Arabic by foster children. With this program, it is expected that foster children can develop their Arabic language skills independently and improve their academic potential and communication skills.